Combining transcranial direct current stimulation and gravity- supported, computer-enhanced arm training in a chronic pediatric stroke survivor: a case report. Issue 1 (2016) - Straudi, Sofia; Chew, Effie; Iahn, Cajigas; Fregni, Felipe; Bonato, Paolo
No abstract available